2012
DOI: 10.7150/ijbs.4096
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Complete Mitochondrial Genome Sequence of Spirometra erinaceieuropaei (Cestoda: Diphyllobothriidae) from China

Abstract: Sparganosis, caused by the plerocercoid larvae of members of the genus Spirometra, can cause significant public health problem and considerable economic losses. In the present study, the complete mitochondrial DNA (mtDNA) sequence of Spirometra erinaceieuropaei from China was determined, characterized and compared with that of S. erinaceieuropaei from Japan. The gene arrangement in the mt genome sequences of S. erinaceieuropaei from China and Japan is identical. The identity of the mt genomes was 99.1% between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
22
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 37 publications
7
22
1
Order By: Relevance
“…However, some species of this genus cannot be reliably differentiated according to these criteria (Knight, 1984). mt genome sequences may provide reliable genetic markers in examining taxonomic status of nematodes (Blouin, 2002), particularly when PCGs sequences are used as markers in comparative analyses Liu et al, 2011;2012c ;Wang et al, 2011). Therefore, in the present study we determined the complete mt genome sequences of T. ovis and T. discolor.…”
Section: Discussionmentioning
confidence: 98%
“…However, some species of this genus cannot be reliably differentiated according to these criteria (Knight, 1984). mt genome sequences may provide reliable genetic markers in examining taxonomic status of nematodes (Blouin, 2002), particularly when PCGs sequences are used as markers in comparative analyses Liu et al, 2011;2012c ;Wang et al, 2011). Therefore, in the present study we determined the complete mt genome sequences of T. ovis and T. discolor.…”
Section: Discussionmentioning
confidence: 98%
“…Mitochondrial DNA sequencing is now considered a useful molecular tool for inferences of evolutionary analysis, phylogenetic reconstruction, taxonomic identification, biogeography, population genetics, and epidemiological investigation [ 3 , 4 ]. The complete mitochondrial genomes of order Pseudophyllidea have been recently published for Diphyllobothrium latum [ 5 ], Diphyllobothrium nihonkaiense [ 6 ], and S. erinaceieuropaei [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mtDNA cox1 gene sequences revealed that S. erinaceieuropaei and S. proliferum are distinct species [ 10 ]. More recently, the complete mitochondrial genome of S. erinaceieuropaei isolated from China was reported and compared to the mitochondrial genome of a Japanese isolate [ 7 ]. However, the speciation of the parasite may need to revise careful reconsideration based on morphological analyses of Spirometra tapeworms.…”
Section: Introductionmentioning
confidence: 99%
“…Previously there has been a paucity of molecular data for S. erinaceieuropaei ; reports in the literature have focused on the mitochondrion [ 41 ]; a small number of cloned nuclear genes, such as genes encoding copper/zinc-superoxide dismutase [ 42 ] and a ced-3-like apoptosis-related gene [ 43 ]; and a survey of 910 ESTs [ 44 ]. Recently, the genomes of four different species of tapeworm were described [ 2 , 3 ] but, for the first time, a genome from the Diphyllobothriidea order of tapeworms is now available.…”
Section: Discussionmentioning
confidence: 99%
“…We found that 7% of the genome was below 0.6× median coverage, and 8% was above 1.6× median coverage. For the mitochondrial genome, we found that 137 contigs in a BLAST search against the mitochondrial sequence of a Chinese isolate [ 41 ] gave a significant match with an E value of <1e-50.…”
Section: Methodsmentioning
confidence: 99%